Identifikasi Pengelolaan Acara Masyarakat Menggunakan Metode Assetbased Community Development: Studi Kasus Pulau Sibandang - Sihombing, Bernadet; Sari, Indah Clara; Fatimah, Meizar Nur (Jurnal Locus Penelitian dan Pengabdian, 2026)
This study explores the application of the Asset-Based Community Development (ABCD) framework in supporting community-based event management in Sibandang Island. As a part of the Toba Caldera UNESCO Global Geopark, Sibandang Island holds cultural and natural significance yet faces challenges in mobilizing local capacity for tourism events such as the annual community festival (pesta rakyat). Using a qualitative approach, data were collected through interviews with residents, community leaders, and organizers, and analyzed using NVivo to map community assets. Findings show six primary asset categories: human, social, economic, physical, natural, and cultural-spiritual assets. The integration of these assets supports the 3A elements in tourism (Attraction, Accessibility, Amenities) but also reveals gaps in infrastructure and capacity. Despite challenges in logistics, infrastructure, and management capacity, the ABCD approach enabled strong community ownership and enhanced social cohesion.